2002
DOI: 10.1093/jexbot/53.373.1397
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the grape dihydroflavonol reductase gene and analysis of its promoter region

Abstract: Dihydroflavonol reductase (DFR) is a key enzyme involved in anthocyanin biosynthesis and proanthocyanidin synthesis in grape. DFR catalyses the reduction of dihydroflavonols to leucoanthocyanidins in the anthocyanin pathway. The DFR products, the leucoanthocyanidins, are substrates for the next step in the anthocyanin pathway and are also the substrates for the proanthocyanidin pathway. In the present study the promoter of the grape dfr gene was cloned. Analysis of the dfr promoter sequence revealed the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
122
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 58 publications
10
122
1
2
Order By: Relevance
“…There are numerous structures and anthocyanin profile has been reported in different plant species [11,12].…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…There are numerous structures and anthocyanin profile has been reported in different plant species [11,12].…”
Section: Chemistrymentioning
confidence: 99%
“…They are glycosides of polymethoxy and polyhdroxy derived of flavylium salts or 2-phenylbenzopyrylium [19]. So far 600 dissimilar entities of anthocyanins have been discovered from different species and this quantity is still rising with the recent advancements in research [11,12,15]. In the plant kingdom, it was documented that through methylation of the six ordinary anthocyanidins, approximately 90% of the anthocyanins were modified of three methylated anthocyanidins, malvidin, petunidin and peonidin, comprised of 20% of the overall described anthocyanidins [17].…”
Section: Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have published reports on the transformation of Vitis [33][34][35][36][37][38][39][40]. To date, Gollop et al [41] have provided evidence for the stable transformation of non-embryogenic cultures (NEC). Nevertheless, the transformation success rate and long-term sustainability of the established transformed cell culture did not seem to be a crucial requirement in their study, and neither was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Many anthocyanin biosynthetic genes are induced by sugars (Gollop et al, 2001(Gollop et al, , 2002Martin et al, 2002;Hiratsu et al, 2003). Expression of the petunia (Petunia hybrida) chalcone synthase (CHS) gene in transgenic Arabidopsis leaves is induced by sugars.…”
Section: Introductionmentioning
confidence: 99%